2006
DOI: 10.1121/1.4787740
|View full text |Cite
|
Sign up to set email alerts
|

The acoustic characteristics of infant cries

Abstract: The present study measured the acoustic characteristics of infant cries. Twenty-eight infants participated, ranging from 2 to 23 months of age. Crying was elicited when their mother moved to a distance, leaving them in the lap of unknown person. The cries were recorded with a microphone placed 1 m from the infant’s mouth in an anechoic room. Analysis of the recorded cries revealed four patterns: cries were classified as either voiced or breathy, and as higher or lower than 7 kHz. Certain cry characteristics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, use of the dynamic time warping (DTW) based approach is presented to investigate the class seperability of different cry modes through the nature of the optimal warping path in DTW algorithm. Other significant studies in infant cry analysis literature are reported in [2,4,7,[9][10][11][12]14,16,18,20,28,32,38,40,43,50,53,55,56]. …”
Section: Introductionmentioning
confidence: 98%
“…In addition, use of the dynamic time warping (DTW) based approach is presented to investigate the class seperability of different cry modes through the nature of the optimal warping path in DTW algorithm. Other significant studies in infant cry analysis literature are reported in [2,4,7,[9][10][11][12]14,16,18,20,28,32,38,40,43,50,53,55,56]. …”
Section: Introductionmentioning
confidence: 98%